Historical review of seaweed research in Malaysia before 2001. - Bujang, Japar Sidik (2012)
This historical account includes the seaweed researches made in Malaysia for the last 40 years. The studies are various and covers aspects from taxonomy, distribution, diversity, environmental background, utilization, aquaculture, and so on. The seaweed taxa recorded in Malaysia (including Singapore) until 2000 include 6 families, 14 genera, 20 species of Cyanophyta, 13 families, 25 genera, 85 species of Chlorophyta, 20 families, 49 genera, 87 species of Rhodophyta, and 8 families, 16 genera, 55 species of Phaeophyta. The other information concerning distribution, habitat condition, species composition, cover, zonation or cultivation, etc. is summarized and tabulated.